Functional MRI Neural Activation Patterns in Early and Late Talkers - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Neural activation patterns, produced while listening to and reading words and non-words, were evaluated by functional MRI in 48 school children, mean age 8 years, in a study at Yale School of Medicine, New Haven, CT.